2018
DOI: 10.1166/jbn.2018.2581
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Delivery System of Cyclovirobuxine D for Brain Targeting: Angiopep-Conjugated Polysorbate 80-Coated Liposomes via Intranasal Administration

Abstract: The blood-brain barrier (BBB) poses a challenge for the treatment of cerebrovascular diseases including cerebral ischemia-reperfusion injury, Parkinson's syndrome, and cerebral tumors. Nanotechnology has developed as a promising strategy for drug delivery applications to the brain, especially liposomes (Lps) that have shown an intrinsic ability to cross the BBB. Angiopep-2 (ANG), a ligand for low-density lipoprotein receptor-related protein-1 (LRP1), is a good prospect for use as a targeting ligand for brain d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In addition, CVB-D could regulate calcium levels inside the cells (23). Previous studies have suggested that calcium levels play an important role in tumor growth, apoptosis and differentiation (24)(25)(26). The hypothesis that CVB-D can promote tumor apoptosis by affecting calcium ion channels can be further explored in future studies and can aid the investigation of the antitumor activity of this compound.…”
Section: Cvb-d Is the Main Active Component Of The Traditionalmentioning
confidence: 99%
“…In addition, CVB-D could regulate calcium levels inside the cells (23). Previous studies have suggested that calcium levels play an important role in tumor growth, apoptosis and differentiation (24)(25)(26). The hypothesis that CVB-D can promote tumor apoptosis by affecting calcium ion channels can be further explored in future studies and can aid the investigation of the antitumor activity of this compound.…”
Section: Cvb-d Is the Main Active Component Of The Traditionalmentioning
confidence: 99%
“…Besides, there was a better targeting and higher AUC of CVBD in the brain after T80-An2-CVBD-Lps by intranasal administration. [15][16][17] Based on the superiority of nasal administration and nano preparations, therefore, this study focused on the protection of CVBD brain-targeted liposomes in CIRI to clarify the target and molecular mechanism of CVBD in treating CIRI, which can lay a foundation for innovative research and development of TNCM.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Nanotechnology-based drug delivery systems with good solubility, high bioavailability, less patient variability and prolonged circulation time provide new therapeutic strategy for AD with brain targeting TCM delivery across through the BBB. [20][21][22] A substance assisting in targeting drug delivery into the brain is Tween 80 (polysorbate 80), which is commonly coating the surfaces of nanoparticles for drug load and delivery. 23 Tween 80 can adsorb apolipoprotein E and enable the binding to the lipoprotein receptor-related proteins (LRPs).…”
Section: Introductionmentioning
confidence: 99%